Evaluating the rheological properties of a synthentic based mud formulated from Avocado Pear Oil (2024)
With the oil and gas sector increasingly focusing on deep offshore drilling in challenging conditions, there is a requirement to create drilling fluids that can perform exceptionally well in such environments. It is crucial to take into account the proper disposal of drilling fluid waste in compliance with environmental regulations. Synthetic-based muds have been suggested as a viable substitute for oil-based muds. Also, the majority of studies on synthetic-based muds have concentrated on base oils that are not indigenous to the area. This study investigates the characteristics of a synthetic-based mud derived from avocado pear oil, which is a readily available and abundant resource, and determines its appropriateness for utilisation in offshore drilling activities. Avocado pear oil was obtained, subjected to transesterification, and utilised in the creation of synthetic-based muds with oil-to-water ratios of 70:30, 75:25, and 80:20, respectively. After 24 hours, it was discovered that the electrical stability remained above 400 at temperatures of 1500 °F. The sample with an oil-water ratio of 80:20 exhibited the maximum plastic viscosity at 1500 °F after 24 hours, indicating superior rheological performance at high temperatures compared to the other samples. The sample with an oil-water ratio of 80:20 exhibited the most minimal mud filter cake in comparison to all other samples, making it the optimal choice for preventing formation damage. The pH level exceeded 8, indicating its suitability for drilling operations.